Pengaruh Return on Equity (ROE), Current Ratio (CR), Debt to Assets Ratio (DAR) dan Return on Assets (ROA) Terhadap Return Saham Dengan Harga Saham Sebagai Variabel Moderating Pada Perusahaan Consumer Goods Yang Terdaftar Di Bursa Efek Indonesia - Sihombing, Monang Juanda Tua (Jurnal Mahajana Informasi, 2023)
The  objective  of  the  research  was  to  find  out  and  to  analyze  the influence of Return on Equity, Current Ratio, Debt to Assets Ratio, and Return on Assets simultaneously and partially on Stock Return with Stock  Price  as  moderating  variable  in  146  consumer goods  companies listed in the Indonesia Stock Exchange, and 87 of them were used as the samples. The data were processed by using Kaiser-Meyer-Olkin (KMO) test and analyzed by using multiple linear regression analysis. The result of the research showed that Return on Equity,  Current  Ratio, Debt  to  Assets  Ratio,  and  Return  on  Assets simultaneously had  significant  influence on  Stock Return.  Partially, Return on Equity had positive but insignificant influence on Stock Return, Debt to Assets Ratio had negative and insignificant influence on Stock Return, Current Ratio had negative but significant influence on Stock Return, and Return of Assets had positive but significant influence on Stock Return. From the result of the test on moderating variable, it was concluded that Stock Price was not able to moderate the correlation  of  Return  on  Equity,  Current  Ratio,  Debt  to  Assets Ratio, and Return on Assets with Stock Return.